Spotlight on Ismail Al-Ghanim's Parliamentary Opposition 1948-1958 (Journal of the College of Basic Education, 2023)
In the summer of 1998, I began collecting historical material for my research topic, entitled((Lights on Ismail Al-Ghanim's Parliamentary Opposition 1948-1958).It is a historical study with analytical features of this political opposition, and of a personality who did notPens are rarely known after their way, however, difficulties impeded the implementation of the project.Foremost among them is the scarcity of information related to the life of this character and her first roles.I found what I wanted at that time in the history books and documents I resorted to, just as I did not find it in the Al-Ghanim family.and those close to him, in addition to the refusal of some of them to inform me of what was available or inconveniences.personality and separate thoughts that the translator left for him, so I postponed the topic, but various motives favoredI had the ball again... as if that was the year we were in, so I re-contacted his familyI collect the simple from what I have available, and I was lucky to find a good group ofHis newspaper (Al-Afkar), which was published in 1954, in addition to those fragments that I picked up fromHistorical documents and sources... In addition to the historical material that I previously collected onMinutes of Parliament sessions, from 1948 to 1958, which are:The period of time in which Al-Ghanim held membership in the Parliament, which is a rather rich material....The research was titled ((Parliamentary Opposition)) to include those positions and roles thatHis interpreter in the parliament was active in it, and to varying degrees... appeasement at times and moderationsometimes, critical seriousness in general, and sometimes excessive negativity...all of which are invitations I want to makeThe representative we are about to correct the crooked actions of the authority and criticize what they are, in order toHe pushed it towards general reform in internal affairs, first according to his political vision and the nature of his ideas.The authority adopts a foreign policy that is consistent with the national and national aspirations of the people.according to his convictions of its feasibility, with the necessity that this policy not be affected by foreign influence, especiallySecond...Based on this, the research included two sections, the first of which is preliminary and the second is basic.(in two related parts)